Genius and Art: Kant’s Theory of Genius and the Concept of Genius in Ukrainian Fictionalized Biographies of Artists - Oksana Levytska (Kyiv-Mohyla Humanities Journal)
The article is dedicated to analyzing the nature of genius in the context of the development of fiction about artists. From the biographies of the famous Renaissance artists by G. Vasari, who made one of the first attempts at chronicling the lives of geniuses of his time, to modern fictionalized biographies of genius artists – we can trace the desire of writers to comprehend the nature of the artists and sculptors’ genius. The foundation of the concept of genius can be found in Immanuel Kant’s works, which synthesized theories developed previously and influenced the understanding of genius by future generations. The paper analyses the consonance of Kant’s aesthetics with the concept of genius in fictionalized biographies of F. Goya, M. Bashkirtseva, V. van Gogh, P. Gauguin, O. Novakivskyi, K. Bilokur, P. Picasso, V. Tsymbal, S. Karaffa-Korbut and other artists, while focusing on the Ukrainian texts of the 20th–early 21st centuries. The research attempts to single out and analyze elements of conceptualizing the notion of genius in novels, including the concepts of the beautiful and the sublime in art, recognition of genius in society, the gender aspect of genius, the issues of heredity, and others. The representation of the image of genius in visual arts, iconography, and the cult of genius are discussed within an intermedial framework.